Influencing Factors for Malnutrition in Chronic Kidney Disease Patients: A Systematic Review and Meta-Analysis - Shengrui, Zhu; Mohd Yusoff, Dariah; Cheng, Kueh Yee; Yusoff, Hafzan; Hongfang, Chen; Wenzhen, Tang (Jurnal Gizi dan Pangan, 2024)
This study reviewed the evidence on influencing factors for malnutrition in Chronic Kidney Disease (CKD) patients. A systematic search of PubMed, Web of Science, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and Wanfang Data Knowledge Service Platform for English and Chinese language observational studies published from 1966 to 2022 was conducted. RevMan 5.4.1 software was used for statistical analysis. A total of 13 observational studies with 7,790 study participants were included in the systematic review and meta-analysis. Seven risk factors and two protective factors related to malnutrition were identified. Age (OR=1.29; 95% CI:1.03–1.61), required feeding assistance (OR=3.33: 95% CI:2.55–4.35), living status (with family) (OR=0.49; 95% CI:0.34–0.71), protein intake (OR=0.89; 95% CI:0.85–0.94), comorbidities (OR=1.78; 95% CI:1.03–3.07), long dialysis duration (OR=1.61; 95% CI:1.16–2.24), inadequate dialysis (OR=1.25; 95% CI:1.12–1.40), hemoglobin level (OR=1.84; 95% CI:0.92–3.66), and depression (OR=3.44; 95% CI:2.21–5.34) were associated with an increased influence of malnutrition among CKD patients. This review provides comprehensive evidence of potential influencing factors of malnutrition among CKD patients